PERILAKU MEROKOK GURU DALAM LINGKUNGAN SEKOLAH DI KECAMATAN TOBELO SELATAN, KABUPATEN HALMAHERA UTARA - Eppi Manik; Marton Tasiringan; Radios Simanjuntak (JURNAL PENDIDIKAN ROKANIA, 2022)
Smoking is a behavior that can have a negative impact both for smokers and for the people around. Various government policies have banned smoking in schools. However, the smoking behavior is still easily found in a number of schools. The study aims to know the percentage number of schools where teachers smoke in school area, to know the students' perceptions of teacher smoking behavior in schools and to know the understanding of headmasters towards smoking-free areas in schools. The research was conducted in Tobelo Selatan District, North Halmahera Regency in June - September 2020. The data was collected by in-depth interviews with 60 randomly interviewed students and 10 headmasters from elementary to high school levels. The results showed that 80% of schools have teachers who smoke in schools, all students disagree with the smoking behavior of teachers in schools, and all headmasters do not know of the no-smoking areas policy in schools.